Living [videorecording (Blu-Ray)] - Ishiguro, Kazuo, 1954-; Nighy, Bill, 1949-; Wood, Aimee Lou, 1995-; Sharp, Alex, 1989-; Burke, Tom, 1981-; Rawlins, Adrian; Chris, Oliver, 1978-; Burton, Hubert; Boyle, Zoe; Fishwick, Barry; Ferran, Patsy; Cochrane, Michael; et al. (Sony Pictures Home Entertainment, 2023)
The story of an ordinary man, reduced by years of oppressive office routine to a shadow existence, who at the eleventh hour makes a supreme effort to turn his dull life into something wonderful.